Foreword - McFadden, Daniel L. (American Economic Review, 2005)
Organizing the program for the annual meetings is by far the most important job of the President-elect.The job is like that of a journal editor, in that the actual content of the program comes from submissions by members, but the importance given to various research and policy areas by program committee members and their reviews of submissions are critical.In addition to organizing the usual program of oral sessions and selecting sessions for inclusion in this volume, committee members assisted me in setting up a series of tutorials on research and policy topics that gave the AEA membership overviews of subjects outside their specialties, and poster sessions that gave more economists opportunities to present their research and meet peers working on similar problems.My program committee was broadly representative of the profession; its members were Alan Auerbach (UC Berkeley, public